STRESS FACTORS AND THEIR COPING STRATEGIES AMONGST THE STUDENTS OF AZAD JAMMU KASHMIR MEDICAL COLLEGE MUZAFFARABAD: A CROSS SECTIONAL STUDY - Mumtaz, Ayasha; Sherwani, Bushra; Sadiq, Muhammad Shakil; Salaria, Sarosh Majid (Pakistan Journal of Physiology, 2018)
Background: Medical studies are known to be highly stressful. Since students get information in Medical Education regarding Health and Development they are also taught the application of necessary skills for them to overcome stress. The aim of this study was to identify various stress factors subjectively, along with the coping strategies in Medical students. Methods: The study was conducted at Azad Jammu and Kashmir Medical College, Muzaffarabad. All students of the college were included in the study. Two questionnaires were developed; first to identify the major sources of stress and coping techniques employed by the students and the second for identification of the factors related to the role of Medical College in reduction of stress in students. Data was collected on 5 point Likert Scale and analyzed on Microsoft Excel in percentage. Results: Response rate was 65%. Long hours in college were detected as the biggest stressor. Absence of Wi-Fi was the second. The modular system of curriculum was not found to be a major source of stress for the students. Coping skill used most frequently was Namaz/Nawafil, followed by interactions with friends and family. Conclusion: The integrated, modular system appeared to be well accepted by the students. Religion and social support provide help in coping with the stress of medical studies. Pak J Physiol 2018;14(2):50–2